The Impact of Motivation and Work Environment on Employee Performance - Achmad Daengs GS*; Enny Istanti; Diana Zuhro; Rina Dewi; Sutini Sutini (Universitas Syiah Kuala, 2024)
This research was motivated by a decline in performance at Nafisa Production in Surabaya. Because Human Resources are central figures in organizations and companies. For management activities to run well, the company must have knowledgeable and highly skilled employees and efforts to manage the company as optimally as possible so that employee performance improves. The more employees have high performance, the overall productivity of the company will increase so that the company will be able to survive in global competition. The purpose of this study is to determine the influence of motivation and work environment on employee performance. Through the questionnaire method by distributing questionnaire questionnaires to 35 respondents of Nafisa Production employees in Surabaya. Based on data analysis and hypothesis tests simultaneously in this study, it can be found that motivation (X1) and work environment (X2) have a simultaneous effect on employee performance (Y), this can be proven by the F value of the calculation (23,380) the F table (2,034). Meanwhile, the R multiple value of 0.771 shows that the relationship between the independent variable and the bound variable is 77.10%. Meanwhile, the value of the multiple determination coefficient is 0.594 which means that all independent variables can explain employee performance (Y) of 59.40%. Motivation partially affects the performance of Nafisa Production employees, this can be seen from the t-value of motivation (X1) which is greater than the work environment variable which is only 2.918. Thus, it is concluded that motivation and work environment have a significant influence on the performance of NAFISA Production Surabaya employees.